Інженерія відновлюваних джерел енергії - Стойка, В. О.; Пономарьов, А. К.; Штих, І. А. (ХНУРЕ, 2018)
The given work describe a renewable energy sources such as wind, sun-light, water waves and tides. It is a necessary to use renewable resources – cata-lyzer for a new generation of technologies and production – in large-scale per-spective. Attention in article is drawn to new methods of energy production, fos-sil fuel dependencies reduction, global warming level reduction and so forth. Fi-nally, the conclusion line is set.
Keywords: відновлювальні джерела енергії; електроенергія; турбіни